The effect of an early oral stimulation program on oral feeding of preterm infants - Tian-chan Lyu; Yu-xia Zhang; Xiao-jing Hu; Yun Cao; Ping Ren; Yue-jue Wang (Elsevier, 2014)
Purpose: To evaluate the effect of an oral stimulation program on preterm infants. Methods: Preterm infants (n = 72) were randomly assigned to experimental and control groups. Controls (n = 36) received routine care while the experimental group (n = 36) received oral stimulation in addition to routine care. Postmenstrual age, total intake volume, body weight, the transition time from initiation of oral feeding to full oral feeding and feeding efficiency were calculated. Results: Postmenstrual age and full oral feeding weight were significantly lower in the experimental group (p < 0.05). The time from initiation of oral feeding to full oral feeding was significantly shorter in the experimental group (p < 0.05) while feeding efficiency was higher in the experimental group (p < 0.05) compared to controls. No significant differences existed in hospital stay length or weight gain rate. Conclusions: An early oral stimulation program is beneficial in preterm infants.